Design optimization of pangolin inspired composites for enhanced energy absorption - Iman Karami Fath; Abbas Niknejad; Hadi Zare-Zardini (Scientific Reports)
Abstract The demand for lightweight, high energy absorbing materials has increased, especially for high risk applications such as aerospace, transport and nuclear. This study aims at analyzing the design and behavior of biomimicking composite structures for structural applications based on the dermal armor system of pangolin under quasi-static loads. We consider two plant-based fibers, luffa and linen, as environmentally friendly substitutes for glass fibers. Using Taguchi, we quantitatively investigated the effects of five factors: fiber type, curvature radius, number of composite plies, trapezoidal scale Y1, and trapezoidal scale Y2 on TAE and SAE. Lateral compressive loads were applied to composite specimens prepared using unsaturated isophthalic polyester resin. It was observed that luffa fibers possess higher TAE and linen fibers possess higher SAE. The Taguchi method set the optimal values for the parameter levels for the prediction of TAE of 11.2431 J and SAE of 2.3677 J/g, while the actual experimental result brought the percentage of error to 5.76% for TAE and 3.94% for SAE. From the theoretical analysis of the RPP and Hollomon models, we gain insights into the energy dissipation process, such as curvature reduction and plastic hinge formation. It is hoped that this work will help to open up a wider field of bio-inspired designs for high-performance sustainable materials; in particular, the proposed framework provides clear ways of predicting the energy absorption characteristics of such structures.